Environmental Enteric Dysfunction as a Risk Factor for Growth Failure in the Agricultural Areas of Brebes Regency - Gandha Sunaryo Putra; Suhartono; Cahya Tri Purnami; Martha Irene Kartasurya (Universitas Airlangga, 2026)
Background: Growth faltering in early childhood remains a global concern. Major contributing factors include poor sanitation, recurrent infections, a history of low birth weight (LBW), and environmental enteric dysfunction (EED) that reduces nutrient absorption. This study examines the determinants of growth faltering among children aged 6–23 months in the agricultural areas of Brebes Regency, Indonesia. Methods: This study employed a case–control design involving non-stunted children aged 6–23 months. The case group consisted of 64 children with weight-for-age (WAZ) < 5th percentile, while the control group included children with WAZ ≥ 5th percentile, classified according to the WHO Child Growth Standards. Data were collected through anthropometric assessments and standardized, structured interviews, with participants selected through purposive sampling. Multivariable logistic regression analysis was performed to identify the determinants of growth faltering. Results and Discussion: There were no significant differences between groups in mean maternal age, child age, or maternal employment status. Maternal education levels were lower in the case group. Acute respiratory infection (ARI) (OR = 2.3; 95% CI: 1.10–5.08), history of LBW (OR = 4.9; 95% CI: 1.21–19.94), and EED (OR = 2.0; 95% CI: 0.93–4.32) were identified as determinants of growth faltering among children living in the agricultural areas of Brebes Regency. Conclusion: EED is a key determinant of growth faltering among children aged 6–23 months in the agricultural areas of Brebes Regency, alongside recent ARI and a history of LBW. Keywords: Brebes Regency, Environmental Enteric Dysfunction, Growth failure, Low Birth Weight, Upper Respiratory Tract Infections